COVID-19 Pandemic, Mental Health and Neuroscience New Scenarios for Understanding and Treatment - Palermo, Sara; Olivier, Berend (IntechOpen, 2023)
Even though knowledge about the impact of the pandemic on mental health is still very limited in all countries and is largely based on experiences only partially comparable to the current epidemic, such as those of the SARS or Ebola epidemics, it is likely that the need for intervention will increase significantly in the coming months and years. Scientific research in neuroscience is a growing field. It offers a novel perspective on the relationship between mind and brain and provides novel scenarios for understanding the long wave of the current pandemic. Furthermore, the pandemic has also led to the possibility of implementing remote monitoring and management interventions. This volume uses multidisciplinary approaches to physiological and cognitive mechanisms, medical treatment, psychosocial interventions, and self-management to help illustrate the complex association among the COVID-19 pandemic, neurological manifestations, mental health, and society.